Infantile Anaphylaxis in Korea: a Multicenter Retrospective Case Study - Jeon, You Hoon; Lee, Sooyoung; Ahn, Kangmo; Lee, So-Yeon; Kim, Kyung Won; Kim, Hyun Hee; Kim, Jeong Hee; Yum, Hye Yung; Kim, Woo Kyung; Park, Yong Mean; Song, Tae Won; Kim, Jihyun; et al. (Journal of Korean medical science, 2019)
Anaphylaxis is increasing in young children. The aim of the present study was to analyze the clinical characteristics of anaphylaxis in Korean infants, with a focus on food triggers. The study analyzed the medical records of infants aged 0 to 2 years old who had been diagnosed with anaphylaxis in 23 secondary or tertiary hospitals in Korea. We identified 363 cases of infantile anaphylaxis (66.9% male). Cutaneous symptoms were most prevalent (98.6%), followed by respiratory (83.2%), gastrointestinal (29.8%), and neurologic (11.6%) symptoms. Cardiovascular symptoms were noted in 7.7% of the cases. Most of the cases of anaphylaxis (338; 93.1%) were induced by foods. The most common trigger food was cow's milk and cow's milk products (43.8%), followed by hen's eggs (21.9%), walnuts (8.3%), wheat (7.7%), peanuts (4.8%), other nuts (3.0%), and fish (2.1%). In cow's milk-induced anaphylaxis cases, more than half the cases had cow's milk specific immunoglobulin E (sIgE) levels that were lower than the diagnostic decision points (DDPs), which is 5 kU /L for those under the age of 1 and 15 kU /L for those over the age of 1. In anaphylaxis induced by hen's egg, most of the cases (91.8%) had hen's egg sIgE levels that were higher than the DDP, which is 2 kU /L for those under the age of 2 and 7 kU /L for those over the age of 2. Of the infantile anaphylaxis cases, 46.8% had been treated with epinephrine, and 25.1% had been prescribed an epinephrine auto-injector. Cow's milk is the most frequent trigger food of anaphylaxis in Korean infants. However, we found no significant correlation between the sIgE level and clinical severity. Education is required regarding the importance of epinephrine as the first line therapy for anaphylaxis and on properly prescribing epinephrine for infants with a history of anaphylaxis.